2019
DOI: 10.7150/thno.35458
|View full text |Cite
|
Sign up to set email alerts
|

Integrative multi-omics analysis identifies a prognostic miRNA signature and a targetable miR-21-3p/TSC2/mTOR axis in metastatic pheochromocytoma/paraganglioma

Abstract: Rationale : Pheochromocytomas and paragangliomas (PPGLs) are rare neuroendocrine tumors that present variable outcomes. To date, no effective therapies or reliable prognostic markers are available for patients who develop metastatic PPGL (mPPGL). Our aim was to discover robust prognostic markers validated through in vitro models, and define specific therapeutic options according to tumor genomic features. Methods : We analyzed three PPGL miRNome dataset… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 43 publications
6
44
0
Order By: Relevance
“…miRNAs play an independent role in the pathogenesis and progression of almost all types of cancers, such as non-small cell lung cancer , breast cancer , gastric carcinoma, bladder tumors and may other known tumor types. They are responsible for modulation of their cellular differentiation, as well as in regulating the transcription of their downstream targets [22][23][24][25][26][27][28][29].…”
Section: Ivyspringmentioning
confidence: 99%
“…miRNAs play an independent role in the pathogenesis and progression of almost all types of cancers, such as non-small cell lung cancer , breast cancer , gastric carcinoma, bladder tumors and may other known tumor types. They are responsible for modulation of their cellular differentiation, as well as in regulating the transcription of their downstream targets [22][23][24][25][26][27][28][29].…”
Section: Ivyspringmentioning
confidence: 99%
“…Indeed, we identified some differentially expressed circRNAs in PCC/PGL patients, such as hsa_circ_0000567, hsa_circ_0002897, and hsa_circ_0004473, that bind to miRNA and affect histone methylation; these three circRNAs were also found differentially expressed between the peripheral blood of PCC/PGL patients and healthy donors. Previous studies have shown that the hsa-miR-183/182/96 cluster, hsa-miR-21-3p, hsa-miR-551b-3p, and hsa-miR-202-5p are associated with metastatic risk and progression of PCC/PGLs (Castro-Vega et al, 2015;Calsina et al, 2019). Notably, our study showed that hsa_circ_0000567 may bind to hsa-miR-96-3p and regulate histone methylation, highlighting hsa_circ_0000567 as a diagnostic and prognostic biomarker for PCC/PGL patients.…”
Section: Discussionmentioning
confidence: 99%
“…If patients fail to undergo proper treatment in time, their 5-year survival rate drops below 40% due to excessive catecholamine secretion as well as the development of chemotherapy and radiation therapy resistance (Toledo et al, 2016;Taieb and Pacak, 2017;. As PCC/PGLs are among the most genetically related human cancers with 60% of patients showing family aggregation (Fishbein et al, 2017;Liu et al, 2018;Job et al, 2019), genetic screening is of great value and significance for the diagnosis and prevention of PCC/PGLs (Calsina et al, 2019). Moreover, over 15 genomic and transcriptomic molecules reported to regulate PCC/PGL development, such as SDHx, VHL, TMEM127, HRAS, FGFR1, ATRX, RET, EPAS1, MAX, EGLN1, and NF1, were found mutated in the germline of PCC/PGLs patients (Gill et al, 2011;Castro-Vega et al, 2015;Rednam et al, 2017;Taieb and Pacak, 2017;Remacha et al, 2017;Pang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports focused on introducing the guide strand miR-21-5p's function in HCC, few researches about the passenger strand miR-21-3p. Until recently, reports on the independent function of miR-21-3p gradually increased, which brought us a new understanding of this microRNA (23,24). The independent function of miR-21-3p includes it could be used as a signature in predicting the survival rate of triple-negative breast cancer (25).…”
Section: Discussionmentioning
confidence: 99%